Incomplete democracies in the Asia-Pacific : Evidence from Indonesia, Korea, the Philippines and Thailand - Dore, Giovanna Maria Dora.; Ku, Jae H.; Jackson, Karl D.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This collection presents a varied picture of the state of democracy in Asia, revealing unique findings from a project entitled the'Asia Democracy Initiative' which explored the role of ordinary people in democratization through the rise of expressive social values in Indonesia, South Korea, the Philippines and Thailand.
Keywords: Science